Offers of food for Spain : inter-departmental correspondence (copy) - Carthy, A. E.
032-0093-001 A.E. CARTHY Mr. H.V. TEWSON INTERNATIONAL 28th February, 1939. OFFERS OF FOOD FOR SPAIN. CROSSE & BLACKWELL (Mr. Moore): Mr. Moore called here yesterday (Monday) and offered the following quantities of trial food lines, packed in this country, which they can offer at cost price:- (The sample shews the size of the meat soups & "Ready Meals"): Herrings in beans in tomato sauce (14 oz.): 115 dozen at 2/10d doz. 16.5.10 "Ready Meals" - vegetable hot pot (about 8 oz.): 1,600 dozen at 2s.4d. dozen. 186.13.4 Kippers: 546 dozen at 2s. dozen - ½ lb. size. 54.12.0 1,500 dozen at 2s.6d. dozen - 1 lb. size. 187.10.0 Concentrated meat soups: (1,000 dozen each mulligatawny, oxtail, mixed vegetables, gravy). 4,000 dozen at 2s.7d. to 2s.8d. dozen. 516.13.4 Herrings: 600 dozen at 3s. dozen. 90.0.0 Green pea soup: (20 oz.): 1,600 dozen at 3s. 3d. dozen 260.0.0 The total cost of this consignment is £1,311.14.6 The offer is open until Friday. POTATO MARKETING BOARD: Mr. Short, of Potato Marketing Board, 'phoned this morning to ask whether we could make use of any potatoes for consignment to Spain. He can offer up to 4,000 tons (of which about 1,000 tons in Scotland) at a price of 30s. a ton free bags on board ship in any Yorkshire, Lincolnshire or Scottish port. The approximate price at Liverpool or Southampton would be 35s. to 37s.6d., but he suggests if we wish to buy and wish to despatch from any port not in Yorkshire, Lincolnshire or Scotland, we 'phone him (Holborn 9152) and ask for a price. I informed him that we would endeavour to give him a reply tomorrow. 292/946/32/93